2014
DOI: 10.1021/jz501392m
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Affecting IV Hysteresis of CH3NH3PbI3 Perovskite Solar Cells: Effects of Perovskite Crystal Size and Mesoporous TiO2 Layer

Abstract: Current-voltage (I-V) characteristics of CH3NH3PbI3 perovskite solar cells are studied using a time-dependent current response with stepwise sweeping of the bias voltage. Compared with the crystalline Si solar cell showing time-independent current at a given bias voltage, the perovskite solar cells exhibit time-dependent current response. The current increases with time and becomes steady at forward scan from short-circuit to open-circuit, whereas it is decayed and saturated with time at reverse scan from open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
738
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,017 publications
(801 citation statements)
references
References 30 publications
(49 reference statements)
46
738
4
4
Order By: Relevance
“…This improved extraction can prevent the accumulation of excess capacitive charge that leads to hysteresis. 19 This explanation is supported by the observation of an increased hysteresis appearing at very fast scan rates ( Figure S3) 35 when settling time is insufficient to eliminate the effect of stored charge. PCBM may also be passivating interface states that trap charge carriers, both at the junction 26 and at grain boundaries.…”
Section: Applied Physics Letters 106 143902 (2015)mentioning
confidence: 85%
See 1 more Smart Citation
“…This improved extraction can prevent the accumulation of excess capacitive charge that leads to hysteresis. 19 This explanation is supported by the observation of an increased hysteresis appearing at very fast scan rates ( Figure S3) 35 when settling time is insufficient to eliminate the effect of stored charge. PCBM may also be passivating interface states that trap charge carriers, both at the junction 26 and at grain boundaries.…”
Section: Applied Physics Letters 106 143902 (2015)mentioning
confidence: 85%
“…16 A two-step interdiffusion approach has recently been shown to result in high quality films in an OPV-style structure. 17 Unfortunately, planar devices have also been shown to be more susceptible to hysteretic effects 18,19 which have been attributed to the migration of ions within the perovskite film. 20,21 The ionic current can arise due to unpassivated trap states that are found at perovskite grain boundaries due to non-ideal formation conditions.…”
mentioning
confidence: 99%
“…c) The time scale of hysteresis is in the range of ≈10 to 100 s, [117,118] which is in great contrast to the typical charge generation/recombination processes (≈ns) in PSCs. [119] d) The hysteresis strongly depends on the external scanning parameters, [120][121][122] such as scan rate, amplitude of external electrical field, scanning direction, pre-scanning conditions, etc. During the last years, different mechanisms have been proposed to be responsible including 1) ferroelectricity, 2) charge trapping/detrapping, and 3) ionic migration.…”
Section: Origin Of Hysteresismentioning
confidence: 99%
“…Several authors have reported on this effect and speculated about the causes. [18][19][20][21][22] Some recent articles present cell designs that minimize this hysteresis. 23,24 In this article, we describe the hysteresis effect in additional detail.…”
Section: Introductionmentioning
confidence: 99%
“…18 All three of these possibilities remain in the debate. 5,19,20,20,25 Along with the addition of crystal size effects 21 . It has been proposed that an optimum mesoporous TiO 2 film thickness minimizes the JV hysteresis.…”
Section: Introductionmentioning
confidence: 99%